How to read Chinese drama : a guided anthology - Sieber, Patricia Angela; Llamas, Regina (Columbia University Press, 2022)
"How to Read Chinese Drama: A Guided Anthology introduces students to the wide world of Chinese theater through excerpts from and context about 14 plays. Special attention is paid to how those plays are realized on stage. These examples cover the entire history of the most important genres up to the maturity of Peking opera in the second half of the nineteenth century. Students will be exposed to many play texts and aspects of Chinese theater, including three types of expressive modes-music (music and singing), text (speaking/reciting/written text), and movements (acting)-historical, biographical, and sociopolitical backgrounds about Chinese drama and playwrights, staging and rituals, and close textual analyses. The book is designed to be used independently or in concert with How to Read Chinese Drama: A Language Text, but the guided anthology volume does not assume any knowledge of Chinese"-- Provided by publisher.
Keywords: Chinese drama -- History and criticism.; Chinese drama -- Translations into English.; Théâtre chinois -- Histoire et critique.; DRAMA / Asian / General; Chinese drama; Criticism, interpretation, etc.; Translations